The study of conformational changes in photosystem II during a charge separation - Kulik, Natalia; Kutý, Michal; Řeha, David (Journal of molecular modeling, 2020)
Photosystem II (PSII) is a multi-subunit pigment-protein complex and is one of several protein assemblies that function cooperatively in photosynthesis in plants and cyanobacteria. As more structural data on PSII become available, new questions arise concerning the nature of the charge separation in PSII reaction center (RC). The crystal structure of PSII RC from cyanobacteria Thermosynechococcus vulcanus was selected for the computational study of conformational changes in photosystem II associated to the charge separation process. The parameterization of cofactors and lipids for classical MD simulation with Amber force field was performed. The parametrized complex of PSII was embedded in the lipid membrane for MD simulation with Amber in Gromacs. The conformational behavior of protein and the cofactors directly involved in the charge separation were studied by MD simulations and QM/MM calculations. This study identified the most likely mechanism of the proton-coupled reduction of plastoquinone QB. After the charge separation and the first electron transfer to QB, the system undergoes conformational change allowing the first proton transfer to QB- mediated via Ser264. After the second electron transfer to QBH, the system again adopts conformation allowing the second proton transfer to QBH-. The reduced QBH2 would then leave the binding pocket.
Keywords: Thermosynechococcus; Bacterial Proteins; Plastoquinone; Photosystem II Protein Complex; sinice; simulace molekulární dynamiky; Lipid Bilayers; fotosystém II (proteinový komplex); MD simulations; Proton-coupled reduction; lipidové dvojvrstvy; Cyanobacteria; Photosystem II reaction center; Molecular Dynamics Simulation; bakteriální proteiny